Accidents of influence : writing as a woman and a Jew in America - Rosen, Norma (State University of New York Press, 1992)
Annotation Examines the relationship of post-Holocaust writers to their work in terms of subject, language, imagery, and facing up to the task of writing in a post-Holocaust era. The 32 previously published essays include personal accounts of being a Jewish woman writer in America, and critiques of literature. No index or bibliography. Paper edition (unseen), $10.95. Annotation copyrighted by Book News, Inc., Portland, OR.
Keywords: Jewish women -- United States -- Literary collections.; Jews -- Literary collections.; Juives -- États-Unis -- Anthologies.; Juifs -- Anthologies.; LITERARY COLLECTIONS -- Essays.; Jewish women; Jews; United States; UNITED STATES.; Electronic books.; Literary collections